Production of enzymatic glucose biosensors - Abd. Aziz, Azila (Universiti Teknologi Malaysia, 2006)
For this project, two types of glucose biosensors namely hydrogen peroxide- based glucose biosensor and mediated glucose biosensor have been developed. The performance of a glucose biosensor depends mostly on the immobilization method and support materials that are being used. For hydrogen peroxide-based glucose biosensor, selection of suitable materials for enzyme immobilization was done. Four types of immobilization materials, including chemically-linked PVA, TMOS sol-gel, alumina sol-gel, and freezed-thawed PVA cryogel, were used to immobilize glucose oxidase (GOD) to determine the most appropriate material for GOD immobilization. Generally the membranes had shown good sensitivity except for the chemically cross-linked PVA. However, the main differences with the enzyme immobilization appmethods were enzyme leakage and the values of Km app. Freeze-thawed PVA-GOD was membranes, which showed satisfactory sensitivity and adequate value of Km app chosen as the support material for immobilizing GOD. The enzyme leakage of this type of membrane was improved by reducing enzyme loading. Even though this type of sensor is very simple and easy to construct, it suffers from electrochemical interferences from common electroactive species present in blood such as acetaminophen. Thus, a selective inner layer based on permselectivity was studied. pHEMA, at a cross-linking ratio of 0.043 which resulted in a permselectivity of 10, successfully eliminated acetaminophen interference. Nafion membrane was used as the outer membrane to protect the biosensor. For the mediated based glucose biosensor development, the scopes of work include the preparation of active layer, preparation of external layer and the fabrication of glucose biosensor. Three methods of tethering a mediator to an enzymatic membrane were studied to construct a non-leaking mediated glucose biosensor. The methods were immobilization of glucose oxidase (GOD) and ferrocene redox polymer in cross-linked poly (vinyl alcohol) (CLPVA) with bovine serum albumin (BSA) as a protein stabilizer, immobilization of ferrocene carboxylic acid and glucose oxidase in a sol gel derived silica (SGS) matrix containing cross-linked poly (vinyl alcohol) (CLPVA) and nafion, and lastly multilayered construction of glucose oxidase and redox poly (allylamine) ferrocene utilizing layer-by-layer covalent attachment. After evaluating the biosonser response amperometrically at 0.363V, the first method, which was immobilization of glucose oxidase and ferrocene redox polymer in CLPVA with the addition of BSA was selected for the fabrication of disposable glucose biosensor since this type of sensor provided good responses over a wide range of concentration. Nafion was chosen as the external layer and the works on the fabrication of the glucose biosensor are ongoing.